(untitled) (Journal of Informatics Education and Research, 2024)
Inclusive education is a style of education that attempts to give equitable access to excellent education for children with varying learning needs. It entails placing these children in ordinary classes and ensuring that they are involved in the educational environment. At first, there was a lack of understanding, educational opportunities, and technology, which resulted in the marginalisation and mistreatment of disadvantaged children. Over time, specialised educational institutes emerged. Contemporary perceptions on children with impairments have undergone considerable changes. They attended the same schools as the other students. Experts in the sector now urge for students’ liberty to pursue their own learning goals. With the Salamanca Manifesto, educational equality has become a global phenomenon. It was recommended that countries pass laws forcing all pupils to attend mainstream schools. In order to properly handle the problem in the classroom, educators must have substantial knowledge and have undergone appropriate training in inclusive education. The attainment of inclusive education will remain an unattainable goal as long as there is a lack of qualified instructors. Inadequate teacher training is one of the most common reasons why inclusive initiatives fail. In order to assure the achievement of inclusive education, the administration must promote in-service training. Community members gain immensely from inclusive education when teachers have a high degree of competence, competency, and confidence. It not only contributes to societal growth and development, but it also promotes the participation of disabled students in mainstream education. It is critical to note that pre-service teacher education programs often fail to meet the different requirements of students with varying levels of ability. The educational community was unable to meet the demands to adjust the curriculum. Recently, educators have advocated for professional development opportunities to improve their abilities in delivering inclusive education to all children.